Scalar-Tensor Theories of Gravity and Their Cosmological Applications. - Vieira, Olesya Galkina (2020)
The main subjects of the thesis concern the most known scalar-tensor theory - Brans-Dicke theory, and cosmological models considered in the gravity in the presence of Born-Infeld type scalar fields, which in the present times are often called tachyons. We